Accounting Education, Accounting Profession and COVID-19? - Velinova–Sokolova, Nadya (UNWE Yearbook, 2021)
The COVID-19 pandemic has had a significant impact, especially in terms of the many changes in regulatory and policy aspects, and in particular challenges in the accounting and education sectors. The 2020 academic year is considerably different from previous years and institutions, staff, and students are facing complex challenges. In terms of the impact of the COVID-19 pandemic on different countries’ education systems many differences exist. Online learning is an amalgamation of various pedagogical models instead of any one single model. The purpose of this article is to present the impact of the coronavirus on higher education in accounting, the challenges that students face in online learning and evaluating the impact of COVID-19 on the accounting profession.